PEDOBRINCANDO - Storck, Adriane M.; Rambo, Andréia; Londero, Angélica C.; Oliveira, Carine C. d.; Fernandes, Catiuza A.; Gerhart, Cristiane; Lunardi, Cristina M. F.; Bourscheid, Deise J.; Schnorrenberger, Dionéia I.; Cassel, Elisângela A.; Zago, Francieli; Golfetto, Gabriela; et al. (Salão do Conhecimento, 2013)
Resumo